Análisis discriminativo de la personalidad antisocial mediante la técnica elección de W. Morgenthaler - Diego Vallejo, Raúl De (1992)
In this article, the authors have analised the antisocial personality (301.70; DSM-ID-R) making use of the Rorschach test and the Morgenthaler technique. 105 delinquents and 111 soldiers had been analised. The results explain that there are many diferences between those groups. The Inkblots number Vill and X have more acceptance among soldiers. Delinquents prefered Inkblots VII and IV. Diferences between preferences and rejects were not significanL